Emprendimiento de una microempresa para la producción y comercialización de pasta de cacao en la ciudad de Machala. - Cabanilla Lopez, Karen Andrea (2018)
During the last years the city of Machala has had a remarkable growth at the productive level, which has generated investment opportunities that add value to agricultural production; One of the products that has increased its production in the city is cocoa, which has encouraged the development of the present project of entrepreneurship for the creation of a microenterpraprice that produces and markets cocoa paste. The purpose of taking forward the proposal is to help cocoa producers improve their income, reducing the number of participants or intermediaries who speculate on the prices of the raw material, since the purchase of cocoa beans will be made directly to the producers. producers; additionally it is intended to generate employment sources for the inhabitants of the sector who will be the most favored with the execution of the project. The present business idea focuses on the development of a product with added value, distinctive, innovative and of quality that is organic and natural from the transformation of cocoa beans without applying heat, in order to make the most of the nutritional and antioxidant characteristics of cocoa that benefit the health of people, in order to satisfy consumers who are increasingly demanding with the products they consume and obtain their loyalty. The activities of the microenterprice PASKAO SA will consist in the purchase of cocoa, without any processing to cocoa producers in the area to make cocoa paste that will be later commercialized in the local market, the distribution of the product will be made in the main supermarkets, mini Marquet and shops in the city, seeking the greatest comfort of customers to acquire the product and get more welcome in the market. In this research work describes the design for the start-up of the microenterprice producing and marketing cocoa paste in the city of Machala, specify the stages involved in the production process (drying, peeling, milling, cooling, tempering and packaging) to transform cocoa beans into a finished product such as cocoa paste; The organizational and functional structure of the microenterprice was also determined. A market study was also conducted for the Economically Active Population of the city of Machala, where a probabilistic sampling was obtained to survey 384 people, to determine the tastes, preferences and needs of the target customers and determine the level of acceptance of the product. on the part of consumers. The research corroborated the feasibility of the project on a financial, technical, operational, environmental and social level, verifying the existence of a market niche available with few bidders and the necessary resources to execute the project. In this way, the microenterprice PASKAO S.A aims to position itself as a leader in the market for the production and marketing of cocoa paste, which will generate great opportunities for future development and expansion by opening work places.